Challenges and support factors in managing type 2 diabetes among pregnant women in Thailand: A convergent mixed-methods study - Phonyiam, Ratchanok; Teng, Chiao-Hsin; Sullivan, Catherine; Palmquist, Aunchalee; Hodges, Eric; Cortés, Yamnia; Baernholdt, Marianne (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Sociocultural and behavioral factors have a multifaceted impact on maternal health. In Thailand, cultural influences significantly shape behaviors of diabetes self-management in women. However, the experience of self-managing diabetes in pregnant women with preexisting Type 2 Diabetes Mellitus (T2DM) remains unclear. Objectives: The study aimed to explore challenges and support factors of diabetes self-management among pregnant women with preexisting T2DM in Thailand, and to compare these factors between women in two groups (optimal and suboptimal maternal health outcomes). Methods: A convergent mixed-methods study was conducted at a tertiary hospital (March to October 2022). Eligible participants were Thai pregnant women, aged 20-44, diagnosed with T2DM. Participants first completed a questionnaire and then were interviewed about diabetes self-management. Maternal health outcomes (i.e., gestational weight gain and glycated hemoglobin [HbA1c]) were reviewed and extracted. Descriptive statistics were used for quantitative analysis, while directed content analysis was used for qualitative data. Side-by-side matrices were used to describe the qualitative subthemes with quantitative results. Results: Twelve Thai pregnant women participated in the study, aged 27 to 40 years, with gestational ages ranging from 7 to 38 weeks and T2DM diagnoses spanning from 3 weeks to 10 years. Half of the participants were obese before pregnancy. Weight gain patterns revealed that 41.67% had inadequate gain, 33.33% had optimal gain, and 25% had excessive gain. HbA1C levels indicated that 75% had good glycemic control. Three women achieved optimal weight gain and glycemic control, while nine exhibited suboptimal health outcomes. We identified six main themes: 1) challenges at the individual level in managing diabetes, 2) support factors at the individual level for diabetes management, 3) challenges at the interpersonal level in controlling diet, 4) interpersonal support factors for managing diabetes, 5) challenges at the societal level in accessing healthcare, and 6) societal support factors for healthcare access. Conclusion: The findings suggest that managing diabetes during pregnancy necessitates dynamic, patient-centered care throughout the pregnancy journey. Regarding the clinical implication, it is important to tailor approaches to the Thai context and to prioritize education and boost women’s confidence in managing diabetes throughout pregnancy.